2002
DOI: 10.1074/jbc.m203513200
|View full text |Cite
|
Sign up to set email alerts
|

Natural Trans-spliced mRNAs Are Generated from the Human Estrogen Receptor-α (hERα) Gene

Abstract: The human estrogen receptor-␣ (hER␣) gene is a complex genomic unit exhibiting alternative splicing and promoter usage in a tissue-specific manner. During the investigation of new hER␣ mRNA variants by rapid amplification of 5 cDNA ends, we identified a cDNA in which the acceptor site of exon 1A, into which the different leader exons are normally alternatively spliced, was spliced accurately the 3 extremity of exon 1A (scrambled 1A31A hER␣ cDNA). Reverse transcription-PCR and S1 nuclease mapping analysis revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 46 publications
1
72
0
2
Order By: Relevance
“…The initial reports documented natural trans-splicing between transcripts of the same gene (homotypic) as well as trans-splicing between different genes (intergenic). 3 Further evidence of natural trans-splicing has recently been reported between two copies of a human estrogen receptor gene, 4 between different human cytochrome oxidase transcripts encoded on opposite strands, 5 and between endogenous cell and highly expressed adenoviral genes. 6 Analysis of various genetic databases have revealed a number of chimeric transcripts.…”
Section: Prospectsmentioning
confidence: 99%
“…The initial reports documented natural trans-splicing between transcripts of the same gene (homotypic) as well as trans-splicing between different genes (intergenic). 3 Further evidence of natural trans-splicing has recently been reported between two copies of a human estrogen receptor gene, 4 between different human cytochrome oxidase transcripts encoded on opposite strands, 5 and between endogenous cell and highly expressed adenoviral genes. 6 Analysis of various genetic databases have revealed a number of chimeric transcripts.…”
Section: Prospectsmentioning
confidence: 99%
“…Pre-mRNA splicing is a naturally occurring process during mRNA maturation, which was first seen in trypanosomes, nematodes and recently also in humans (Murphy et al, 1986;Flouriot et al, 2002;Davis et al, 1995). During trans-splicing, the spliceosome ligates a 5' exon from one pre-mRNA with a 3' exon from another pre-mRNA, thereby producing an "alternative" mature mRNA, composed of exons derived from two different precursors.…”
Section: Spliceosome Mediated Rna Trans-splicingmentioning
confidence: 99%
“…Further studies have indicated that many other RNA chimeras are generated from mechanisms such as transcription read-through and splicing, transcription of short homologous sequence slippage or from so called trans-splicing (Table 1) (1). In the aid of high-throughput sequencing technology and bioinformatics analysis, a growing number of chimeric RNAs have been identified and validated during the last two years (2)(3)(4)(5)(6)(7)(8) …”
Section: Introductionmentioning
confidence: 99%